Lateralized connectivity in the alpha band between parietal and occipital sources when spatial attention is externally and internally directed - Van der Lubbe, Rob H. J.; Panek, Bartłomiej; Jahangier, Ivania; Asanowicz, Dariusz (Frontiers in Cognition, 2023)
External spatial attention refers to the selection of currently present information at a specific external location, whereas internal spatial attention refers to the selection of stored information in short-term memory initially presented at a specific location. Electroencephalographic (EEG) and magnetoencephalographic (MEG) studies revealed that these two types of selection may involve the same underlying neural mechanism as in both cases a reduction in posterior alpha power was observed. However, the posterior alpha rhythm may consist of different components, which can even be related to opposite behavioral effects. Furthermore, the employed paradigms to study both selection processes are often quite different, which makes a proper comparison cumbersome. In the current EEG experiment, two-stimulus displays were preceded or followed by non-spatial pre-cues and post-cues that specified the target, thereby minimizing procedural differences. Results of time-frequency analyses revealed that in both cue conditions the selection of relevant information was associated with an increase of ipsilateral vs. contralateral posterior alpha power. An opposite effect, an increase in contralateral vs. ipsilateral posterior power was observed in the theta-band, but only in the pre-cue condition. This activity was related to stimulus onset and likely reflects target selection. To assess attention-related connectivity, we separated posterior alpha power in a medial-parietal and two parieto-occipital sources and computed alpha phase coherence between these sources. Results revealed that in both cue conditions, increased ipsilateral vs. contralateral connectivity in the alpha band was present between the medial-parietal and parieto-occipital sources. The results seem to reflect a modulation from parietal to occipital areas, providing support for the view that internal and external spatial attention share a common neural mechanism.